Realitas Sosial dalam Cerpen Rumah Tepi Kali Karya Dedy Vansophi - Baqiyah, Alvi Khoirul; Astuti, Cutiana Windri; Suprapto, Suprapto (LEKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Social reality is a reality that occurs in society, both from the positive and negative sides. This research aims to examine images of social reality in the short story collection Rumah Tepi Kali by Dedy Vansophi. So the method used in this research was descriptive qualitative. Because it is in the form of words or sentences found in short stories using a literary sociology approach, ascience that studies humans and society. Data collection consisting of words or sentences in the short story was taken using the techique of reading data, clarifying, analyzing and concluding. The results show that the social reality in the short story collection Rumah Tepi Kali by Dedy Vansophi, is in the form of: (i) poverty, (ii) care, (iii) religious, (iv) crime. Keywords: Social Reality, Literary Sociology, Short Story River Edge House